Implementation of Land Registration Procedures in Indonesia Based on Government Regulation No. 18 of 2021 - Aulia Fitri Rahdania; Benny Djaja (Journal of Social Research, 2023)
Soil is inseparable from all activities of living things. Land is also a source of activity for life and human habitation, especially for Indonesian citizens, where the majority of citizens still rely on land for survival, such as for agricultural land and plantations. The purpose of this study is to analyze the application of legal rules regarding land registration procedures based on Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Flats Units, and Land Registration. This research uses the Normative Juridical type of research, which is conceptualized as norms or rules that exist and are obeyed in society, so that they become a reference in behavior. In related arrangements land registration must be based on the principle of legality. In Black's Law Dictionary, legislation/legality has many meanings, one of which is Legislative Action, Drafting and Making Laws and/or Drafting rules for the future. Based on the results of the analysis in this study, it was found that a legal effect was arising related to the implementation of the installation of stakes and related to the principle of delimitation contradictions.